2022
DOI: 10.1037/pas0001057
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and validity of the Inventory of Depression and Anxiety Symptoms-II (IDAS-II) in a chronic back pain treatment-seeking sample.

Abstract: Many patients who seek treatment for chronic back pain are also at a higher risk of having comorbid anxietyand depression-related disorders. Measures of mood and anxiety are routinely used in medical settings to screen for depression-and anxiety-related symptoms. However, factor analyses of other measures of mood and anxiety in medical settings often detect a somatization factor which, in turn, limits their discriminant validity for use across medical settings. The Inventory of Depression and Anxiety Symptoms-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…De la Rosa-Cáceres et al (2020) also observed a second-order factor for the internalizing symptoms. Finally, contrary to all previous studies, Kaye et al (2022) observed a one-factor structure for the inventory. Also, it is important to mention that Cervin et al (2024) found a four-factor solution for a youth sample, which will not be tested in this study, given our focus on adults.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…De la Rosa-Cáceres et al (2020) also observed a second-order factor for the internalizing symptoms. Finally, contrary to all previous studies, Kaye et al (2022) observed a one-factor structure for the inventory. Also, it is important to mention that Cervin et al (2024) found a four-factor solution for a youth sample, which will not be tested in this study, given our focus on adults.…”
contrasting
confidence: 99%
“…We performed restricted factor models with half of the sample, replicating the findings from Cervin et al (2024), De la Rosa-Cáceres et al (2020), Irak and Albayrak (2020), Kaye et al (2022), Watson et al (2012), and Wester et al (2022), Petre et al (2023). We also performed models that added a general factor (hierarchical models) for the models found by Irak and Albayrak (2020), Watson et al (2012), and Wester et al (2022), Petre et al (2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these findings are significant, they are limited by recent research indicating that screening instruments, such as the PHQ, are not specific to depression but are actually indicators of general psychological distress rather than major depressive disorder (Katz et al, 2021; McCord & Provost, 2020). Owing to high comorbidity between psychopathology and chronic pain, instruments used in presurgical psychological evaluations (PPEs) must have high levels of sensitivity, specificity, and discriminant validity for the specific constructs that predict recovery (Block et al, 2013), and some instruments have not met these standards (e.g., Kaye et al, 2022). Whereas many instruments assess negative emotionality, the MMPI-3 includes well-validated scales that measure demoralization (i.e., general distress similar to that measured by the PHQ; McCord & Provost, 2020), low positive emotionality (i.e., anhedonia), negative emotionality, as well as relevant narrower constructs such as malaise, neurological complains, family problems, substance abuse, and anger proneness with good discriminant validity (Ben-Porath & Tellegen, 2020a, 2020b).…”
Section: Influence Of Psychopathology and Personality Traits On Traje...mentioning
confidence: 99%